Perioperative Challenges in Malnourished Geriatric Patients - Jusiak, Justyna; Halik, Paulina; Borszowska-Bartosz , Alicja; Strzyżewska-Kędzierska , Maria (Quality in Sport, 2025)
Introduction. Malnutrition in the geriatric population increases the incidence of postoperative complications, length of hospital stay, recovery time, and mortality. Materials and methods. An analysis of scientific articles published between 2002 and 2025 was conducted to evaluate the impact of preoperative malnutrition on the incidence of perioperative complications. Results. Preoperative diagnosis of malnutrition in the geriatric population is a risk factor for perioperative complications. Malnutrition identified using the Geriatric Nutritional Risk Index (GNRI) is associated with an increased incidence of perioperative complications. Additional predictive factors include hypoalbuminemia, weight loss greater than 10% within six months prior to surgery. Scientific reports also highlight the influence of electrolyte imbalances, such as hyponatremia and hypokalemia, which often accompany malnutrition, on the increased risk of perioperative complications in the elderly. Malnourished elderly patients exhibit higher incidences of postoperative cognitive dysfunction, pneumonia, and impaired wound healing. Discussion. Malnutrition is a significant factor determining the increased risk of perioperative complications in geriatric patients. Individuals with insufficient nutritional status more frequently experience impaired wound healing and surgical site infections. Routine assessment of nutritional status in elderly patients before surgery may facilitate the early identification of those at increased risk of perioperative complications. Such an approach would also enable early nutritional intervention, which could potentially reduce the incidence of complications in this population. Conclusions. Identifying malnutrition in geriatric patients and implementing measures to optimize nutritional status in the preoperative period may reduce the risk of perioperative complications in the elderly population.